2009
DOI: 10.1105/tpc.108.062752
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Redox Imbalance Governs Leaf Sectoring in theArabidopsis thalianaVariegation Mutantsimmutans,spotty,var1, andvar2 

Abstract: We hypothesized that chloroplast energy imbalance sensed through alterations in the redox state of the photosynthetic electron transport chain, measured as excitation pressure, governs the extent of variegation in the immutans mutant of Arabidopsis thaliana. To test this hypothesis, we developed a nondestructive imaging technique and used it to quantify the extent of variegation in vivo as a function of growth temperature and irradiance. The extent of variegation was positively correlated (R 2 = 0.750) with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
146
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(157 citation statements)
references
References 103 publications
11
146
0
Order By: Relevance
“…During de-etiolation, the NDH-like complex rapidly starts to interact with PSI, and after just 48 h in light, the PSI-NDH supercomplex is assembled (Peng et al 2008). This result may support the speculated co-operation between NDH and the plastid terminal oxidase PTOX, which is known to be crucial for the early leaf development and for the proper chloroplast biogenesis (Rosso et al 2006(Rosso et al , 2009. Alternatively, the etioplastic NDH-like complex might be physiologically nonfunctional until the appearance of its assembly partner, PSI.…”
Section: Ndh Complexes In Electron Transfersupporting
confidence: 58%
“…During de-etiolation, the NDH-like complex rapidly starts to interact with PSI, and after just 48 h in light, the PSI-NDH supercomplex is assembled (Peng et al 2008). This result may support the speculated co-operation between NDH and the plastid terminal oxidase PTOX, which is known to be crucial for the early leaf development and for the proper chloroplast biogenesis (Rosso et al 2006(Rosso et al , 2009. Alternatively, the etioplastic NDH-like complex might be physiologically nonfunctional until the appearance of its assembly partner, PSI.…”
Section: Ndh Complexes In Electron Transfersupporting
confidence: 58%
“…Leaf variegation predicts a threshold of unknown factors that determine chloroplast development in a cell-autonomous fashion (e.g., Rosso et al, 2009). We demonstrate that the threshold is determined by the total amount of the FtsH heterocomplex rather than the total number of protease sites.…”
Section: Factors Affecting Leaf Variegation In Var2mentioning
confidence: 96%
“…As early as 1949, Stout observed that induction of the reproductive development of sugar beet is correlated with changes in the oxidation-reduction balance of certain regions of the plant (Stout 1949). Root growth, flowering, development of floral organs, leaf sectoring, and photoperiodism are regulated by the redox potential (Becker et al 2006;Foreman et al 2003;Rosso et al 2009;SanchezFernandez et al 1997;Xing et al 2006). Reactive oxygen species (ROS) are key actors in the regulation of plants' dormancy and germination (Bailly et al 2008).…”
Section: Redox Homeostasismentioning
confidence: 99%